Mutiloculated thymic cyst: unusual presentation of mediastinal mass - Laudari, Uttam; Bhandari, Shreya; Ramtel, Rupesh; Adhikari, Bibhuti; Bhandari, Mohan Dev (Journal of Patan Academy of Health Sciences, 2019)
Here we present a case of 47 year male found to have large multiloculated thymic cyst during work up done for recurrent pleural effusion. Mediastinal cyst constitutes 10-15% of all radiographically detected mediastinal masses. Thymic cyst account only 5% of mediastinal masses. Thymic cyst can cause difficulty in diagnosis due to its rare presentation, invasive nature and occasional associated with thymic neoplasm. They have been detected incidentally and associated with Sjögren’s syndrome, aplastic anemia myasthenia gravis and immunocompromised patients. Here we present a case of 47-year-old male initially work up done for recurrent pleural effusion turned out to be large multilocuated thymic cyst improved after excision which had no associated syndromes and immunocompromised state.